In office dental bleaching with hydrogen peroxide: A case report - Pribadi, Nirawati; Sylvia; Tri Maulinda, Wulan; Wahyu Nur Cahyani, Anggi (Conservative Dentistry Journal, 2022)
Background: Tooth discoloration has become an aesthetic issue that has a psychosocial impact on the majority of people. Dental bleaching is the most conservative preferred treatment for discolored teeth. Purpose: The aim of this case study is to report cases with in-office dental bleaching of maxillary and mandibular anterior teeth. Case: A 35-year-old woman complained about a yellowish tint on her upper jaw and front mandible, which made her feel self-conscious. Case Management: In-office dental bleaching performed using hydrogen peroxide and a desensitizing agent. Follow-up was taken, and the treatment results were satisfactory. Conclusion: In office dental bleaching is a treatment option to correct discolored teeth in a short time.